2012
DOI: 10.1053/j.gastro.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X Receptor Protects Hepatocytes From Injury by Repressing miR-199a-3p, Which Increases Levels of LKB1

Abstract: BACKGROUND & AIMS Hepatocyte injury occurs during liver fibrogenesis. MicroRNAs (miRNA) regulate some of these processes, and some are regulated by the farnesoid X receptor (FXR). We investigated the effect of repression of specific miRNAs by FXR in hepatocyte injury using fibrotic liver tissue from patients and hepatocytes. METHODS We used immunohistochemistry or real-time polymerase chain reaction to analyze proteins and miRNAs in human and mouse liver samples. HepG2 cells were transfected with pre-miRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…26 miR-199a-3p was reported to play a role in hepatocyte injury and hepatocellular carcinoma. 25,38 miR-93* regulates cell proliferation, 39 whereas miR30a is associated with autophagy and apoptosis. 40,41 Spearman analysis in our study demonstrated a high correlation between several miRNAs in the panel, suggesting that the above miRNAs have a similar function in the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 miR-199a-3p was reported to play a role in hepatocyte injury and hepatocellular carcinoma. 25,38 miR-93* regulates cell proliferation, 39 whereas miR30a is associated with autophagy and apoptosis. 40,41 Spearman analysis in our study demonstrated a high correlation between several miRNAs in the panel, suggesting that the above miRNAs have a similar function in the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The 6 altered miRNAs we identified are involved in inflammation, tissue damage, regulation of cell proliferation, and tissue repair, [24][25][26] suggesting increased levels of these miRNAs in the plasma of aGVHD patients may be associated with the immune response and organ damage during aGVHD. We thus evaluated the sensitivity and specificity of these miRNAs in diagnosing aGVHD using ROC analysis.…”
Section: Development Of a Diagnostic Panel Containing 4 Plasma Mirnasmentioning
confidence: 95%
“…FXR KO mice are predisposed to gallstone disease, but activation of FXR ameliorates this condition by restoring the bile acid to cholesterol ratio (16). In humans, FXR expression is markedly reduced in patients with severe cirrhosis and liver cancer (14,15,17). Together, FXR regulatory processes are involved in pathologies ranging from hyperlipidemia to diabetes, from cholestasis to enterohepatic tumors.…”
mentioning
confidence: 99%
“…Activation of FXR increases hepatic levels of miR-144, which in turn lowers hepatic ABCA1 and plasma HDL levels (18). FXR protects hepatocytes from injury by repressing miR-199a-3p and thereby increasing levels of LKB1 (17). Activation of FXR also increases the expression of miR-29a in hepatic stellate cells and inhibits extracellular matrix production (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation